2010
DOI: 10.1038/nsmb.1873
|View full text |Cite
|
Sign up to set email alerts
|

Lys11-linked ubiquitin chains adopt compact conformations and are preferentially hydrolyzed by the deubiquitinase Cezanne

Abstract: Ubiquitin is a versatile cellular signaling molecule that can form polymers of eight different linkages, and individual linkage-types have been associated with distinct cellular functions. Though little is currently known about Lys11-linked ubiquitin chains, recent data indicate that they may be as abundant as Lys48-linkages and involved in vital cellular processes. Here we report the generation of Lys11-linked polyubiquitin in vitro, for which the Lys11-specific E2 enzyme UBE2S was fused to a ubiquitin bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
314
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(334 citation statements)
references
References 50 publications
14
314
0
6
Order By: Relevance
“…K11‐diUb was found to adopt a compact conformation, which is consistent with previous studies (Figure 4D),31 whereas K63‐diUb took on an open conformation (Figure 4E). The structural alignment of wild‐type Ub with the Ub units in K11‐ and K63‐diUb very strongly suggests that all the Ub units adopted the native conformation (Figure 4F,G).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…K11‐diUb was found to adopt a compact conformation, which is consistent with previous studies (Figure 4D),31 whereas K63‐diUb took on an open conformation (Figure 4E). The structural alignment of wild‐type Ub with the Ub units in K11‐ and K63‐diUb very strongly suggests that all the Ub units adopted the native conformation (Figure 4F,G).…”
Section: Resultssupporting
confidence: 92%
“…In vitro Ub enzyme systems were first developed for the preparation of polyUbs, and their utility has been demonstrated by the synthesis of almost all types of Ub chains 15, 28, 29, 30, 31. However, K27‐polyUbs and heterogeneous polyUbs have yet to be accessed with this technology 32.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results not only suggest that Cezanne functions as a tumor suppressor in gliomas but also further support the notion that dysregulation of ubiquitin conjugation/deconjugation is involved in human cancer. Although Cezanne was reported to inhibit NF-κB signaling through removing K63-linked polyubiquitin chains from RIP1 [24,25], Bremm et al [40] found that Cezanne preferentially hydrolyzes K11-linked polyubiquitin chains. Interestingly, a recent study reported that K11-linked polyubiquitin chains of RIP1 can also serve as a platform for recruitment of NEMO and participate in TNF-α-stimulated NF-κB activation [41].…”
Section: Discussionmentioning
confidence: 99%
“…2B) (24). Second, full-length, wild type Trabid hydrolyzes Lys-63-linked chains (24,(37)(38)(39). Third, although Lys-48 and Lys-29 chains were the most abundant ubiquitin polymers that co-precipitated with Trabid C443S, Lys-63 chains were also detected, and the majority of these were present in the HMW regions a and b (Fig.…”
Section: Identification Of E3 Ubiquitin Ligase Hectd1 In a Trabidmentioning
confidence: 99%